A protein with an inactive pterin‐4a‐carbinolamine dehydratase domain is required for Rubisco biogenesis in plants. (December 2014) - Feiz, Leila; Williams‐Carrier, Rosalind; Belcher, Susan; Montano, Monica; Barkan, Alice; Stern, David B.
Summary Ribulose‐1, 5‐bisphosphate carboxylase/oxygenase (Rubisco) plays a critical role in sustaining life by catalysis of carbon fixation in the Calvin–Benson pathway. Incomplete knowledge of the assembly pathway of chloroplast Rubisco has hampered efforts to fully delineate the enzyme's properties, or seek improved catalytic characteristics via directed evolution. Here we report that a Mu transposon insertion in the Zea mays (maize) gene encoding a chloroplast dimerization co‐factor of hepatocyte nuclear factor 1 (DCoH)/pterin‐4α‐carbinolamine dehydratases (PCD)‐like protein is the causative mutation in a seedling‐lethal, Rubisco‐deficient mutant named Rubisco accumulation factor 2 (raf2‐1). In raf2 mutants newly synthesized Rubisco large subunit accumulates in a high‐molecular weight complex, the formation of which requires a specific chaperonin 60‐kDa isoform. Analogous observations had been made previously with maize mutants lacking the Rubisco biogenesis proteins RAF1 and BSD2. Chemical cross‐linking of maize leaves followed by immunoprecipitation with antibodies to RAF2, RAF1 or BSD2 demonstrated co‐immunoprecipitation of each with Rubisco small subunit, and to a lesser extent, co‐immunoprecipitation with Rubisco large subunit. We propose that RAF2, RAF1 and BSD2 form transient complexes with the Rubisco small subunit, which in turn assembles with the large subunit as it is released from chaperonins.